Detection of chikungunya virus infection in monkeys from ther Davao Region - Otero, Maria Catherine B. (2017)
Chikungunya is one pf the most important re-emerging arboviral diseases in the Philippines, causing almost yearly urban outbreaks. Chikungunya is endemic in the Philippines, with episodic transmission. Non-human primates are natural amplification hosts of the Chikungunya virus (CHIKV), and sylvatic or enzootic Chikungunya has been documented in africa and in some parts of Asia. In this study, we sought to establish the presence of Chikungunya in captive and wild long-tailed macaques ( Macaca fascicularis) from a wildlife center in Davai City, an agricultural farm in Kapalong, Davao del Norte, and a beach forest in Tagum City detecting anti-CHIKV antibodies. A total of 61 caged and semi-wild Philippine macaques were captured and bled in the 3 sites. Serum samples were brought for laboratory analyses at RITM. Out of 54 available serum samples,CHIKV IgM was detected in 26 percent of the monkeys, with the highest sub-population prevalence in the captive monkeys from the agricultural farm (39 0ercent). Two of the CHIKV IgM-positive macaques from the agricultural farm were also febrile during sample collection, suggecting that CHIKV infection in these monkeys was detected early in the infection. Out of 49 available serum samples, CHIKV IgG was detected in only 1 monkey. The very low number of CHIKV IgG-positive suggests that the CHIKV infection was captured at the early stages (3-5 days p.i.) of the disease, when IgG is not yet produced. No CHIKV RNA was detected from all samples. Overall results point to a recent CHIKV introduction to the monkey population in the study sites. These results support the sylvatic or enzootic transmission of CHIKV in monkeys in the Philippines. Thus, vector control alone may not be sufficient as other animals can contract CHIKV and be possible vessels for transmission.
Available in CD, pdf copy.
Thesis (Master of Science in Public Health (Medical Microbiology)--University of the Philippines Manila
Keywords: Chikungunya; Monkeys